Assessment of community and local government capacity to coping landslide susceptibility in Babakan Madang District, Bogor Regency - Indarti Komala Dewi; Nabila Al Mujahidah Muhtar (Universitas Pakuan, 2025)
Babakan Madang District is one of the landslide-prone areas in Bogor Regency. Therefore, to anticipate the situation, it is crucial to understand the level of landslide susceptibility and the capacity of the community and local government. High community and local government capacity can reduce disaster risk and increase the community's ability to recover and adapt after a disaster occurs. The objectives of this study are: 1) Identifying the level of landslide susceptibility in Babakan Madang District; 2) Identifying the level of community capacity in Babakan Madang District; and 3) Identifying the level of local government capacity in Babakan Madang District. The data used are secondary data (documents and maps) and primary data (interviews, questionnaires, and observations). Landslide susceptibility analysis uses six parameters, namely rainfall intensity, rock type, soil type, slope gradient, and land use. Community and local government capacity analysis uses four parameters each, namely Facilities and Infrastructure, Human Resources, Economy, and Institutional. The analysis results show that 75.16% of Babakan Madang District has a moderate level of landslide susceptibility, and the remaining 24.84% has a high level of landslide susceptibility. Overall, the level of community and local government capacity is high, but the level of institutional capacity parameters is still low. Therefore, to strengthen disaster risk reduction in Babakan Madang District, the low institutional capacity of the community and local government needs to be improved.